EDUKASI DAN SOSIALISASI PENYULUHAN TENTANG REAKTOR EMBER TUMPUK SEBAGAI SOLUSI PRAKTIS DALAM MENGOLAH LIMBAH RUMAH TANGGA MENJADI PUPUK ORGANIK CAIR (LINDI) - Putri, Candara Nadia; Amanda Nasywa Rachmaddini; Aulia Nikmatul Fauziah; Lam Luthfiyyah Khairun Nisa; Farhan Zaki Naufal Meuraxa; Faris Abdul Majid; Yosevin Tiodora; Sepbela Adek Putri Patresia; Heliana Sapto Yuwono; Afrizal Kaka Pratama (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Food security is an important aspect in improving people's welfare and human development to help alleviate poverty, especially for the people of Desa Bugisan, Prambanan, who have limitations in processing organic household waste, which is also a major focus for improving environmental conditions that will affect the sanitation of the surrounding environment. This Kuliah Kerja Nyata (KKN) work programme will help the Desa Bugisan increase their knowledge and awareness of the importance of food management and food waste reduction, as demonstrated through active community participation. The KKN work programme was implemented by providing education to the surrounding community, especially housewives and the Kelompok Wanita Tani (KWT), about the dangers of food waste and how to process it into liquid organic fertilizer (lindi), in collaboration with Penyuluh Pertanian from the Balai Penyuluh Pertanian Kecamatan Prambanan. The results of this work programme show an increase in awareness of the importance of processing household waste, especially among housewives and the Kelompok Wanita Tani (KWT), and the start of implementing the practice of making liquid organic fertilizer (lindi) using stacked bucket reactors. This work programme also has the potential to boost the economy through the results of the practice of making liquid organic fertilizer (lindi).